Chronic granulomatous disease presenting as refractory pneumonia in late adulthood. Issue 2 (24th March 2015) - Sarwar, Ghulam; de Malmanche, Theo; Rassam, Loui; Grainge, Christopher; Williams, Andrew; Arnold, David
Abstract We present a case of refractory pneumonia in an adult patient with underlying chronic granulomatous disease (CGD). Her lobectomy tissue grew Burkholderia cepacia and histopathology revealed diffuse severe pneumonic consolidation with suppurative/necrotizing granulomata. An initial attempt to find an underlying immune deficiency was unsuccessful. Following recurrent invasive infections, repeat immunological assessment revealed reduced neutrophil function, demonstrating skewed carrier status (lyonization) for X‐linked CGD (only 3% normal cells). A pathogenic mutation in the CYBB gene was found on sequencing. CYBB gene encodes the gp91phox, a catalytic subunit of nicotinamide adenine dinucleotide phosphate‐oxidase that produces reactive oxygen species in phagocytes. Lyonization increases with age, explaining the delayed clinical CGD. CGD is a rare neutrophil disorder that usually presents in early life with recurrent infections due to bacteria and fungi primarily involving lungs and skin. It is secondary to a defective NADPH oxidase system needed to kill intracellular organisms and activate the formation of neutrophil extracellular traps.